Method to Improve Heat Extraction in Enhanced Geothermal Systems with Heterogeneous Fracture Network (Advances in Applied Mathematics and Mechanics, 2024)
In typical EGS fracturing projects, the fracture network is denser in the region close to the fracturing wells. The distribution of fractures has a significant impacton the heat extraction performance of enhanced geothermal system (EGS). In order toavoid premature thermal breakthrough and improve the thermal extraction efficiency,this paper studies the heat extraction performance of EGS in heterogeneous fracturedreservoirs under different injection-production methods. First, a heterogeneous discrete fracture network generation method based on relative pressure distribution isdeveloped. A thermo-hydraulic-mechanical (THM) coupling model is established tosimulate the fluid flow and heat transfer in reservoirs. The heat extraction performanceunder different production and injection modes is compared with different fracturedensities. The results show that injection in the dense side of the anti-parallel wellconfiguration will be more efficient for heat extraction. Under the condition of sameinjection mass flow rate, the heat extraction performance is positively correlated withthe fracture density. Although sparse-side injection is not conducive to fluid flow, under the condition of same injection mass flow rate with anti-parallel well configuration,it will improve the thermal extraction performance.